Menanamkan Pendidikan Karakter dalam Mnghadapi Era Society 5.0 - Dalilah, Zulfi (Journal of Islamic Education Counseling, 2022)
Abstrak: Along with the development of technology, the transformation of education has developed rapidly. It is characterized by current learning which is very closely related to technology, such as the existence of learning systems and methods that are supported by the technology of the digital world. Technology is widely used in supporting education as a means and infrastructure in the interaction between educators and students. Character education is how to build a generation of people who are moral and have good character. Character education is very important in facing the era of society 5.0 which is a challenge in the world of education. Education is not only educating the nation's generation but must cultivate the identity of the nation's children so that they become human beings with morals to create a just, safe and prosperous life. Therefore, education must prepare good digital literacy to equip students so that later they will not stutter in the face of the 5.0 era of society. This research is qualitative research by examining existing literacy sources. This study aims to discuss character education that must be applied in facing the era of society 5.0.